Differential proteomic analysis of white adipose tissues from T2D KKAy mice by LC‐ESI‐QTOF. Issue 5 (March 2017) - Ke, Ming; Wu, Hanyan; Zhu, Zhaoyang; Zhang, Chi; Zhang, Yongqian; Deng, Yunlin
Abstract : Type 2 diabetes (T2D) has become a worldwide increasingly social health burden for its high morbidity and heightened prevalence. As one of the main tissues involved in uptake of glucose under the stimulation of insulin, WAT plays very important role in metabolic and homeostasis regulation. We performed a differential proteomics study to investigate alterations in epididymis fat pad of high fat diet fed T2D KKAy mice compared to normal fed C57BL/6J mice, by 18 O‐labeling relative quantitative technique. Among 329 confidently identified proteins, 121 proteins showed significant changes with CV ≤ 20% (fold changes of >2 or <0.5 as threshold). According to GO classification, we found that altered proteins contained members of biological processes of metabolic process, oxidative stress, ion homeostasis, apoptosis and cell division. In metabolic, proteins assigned to fatty acid biosynthesis (FAS etc.) were decreased, the key enzyme (ACOX3) in β‐oxidation process was increased. Increased glycolysis enzymes (ENOB etc.) and decreased TCA cycle related enzymes (SCOT1 etc.) suggested that glucose metabolism in mitochondria of T2D mice might be impaired. Elevated oxidative stress was observed with alterations of a series of oxidordeuctase (QSOX1 etc.). Besides, alterations of ion homeostasis (AT2C1 etc.) proteins were also observed. The enhancement of cell proliferation associated proteins (ELYS etc.) and inhibition of apoptosis associated proteins (RASF6 etc.) in WAT might contributed to the fat pad and body weight gain. Overall, these changes in WAT may serve as a reference for understanding the functional mechanism of T2D.